2008
DOI: 10.1080/13590840802302826
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a questionnaire to assess dietary habits among 5–13‐year old school children of farmers and anthroposophic families

Abstract: Objective. To evaluate dietary habits among 5-13-year old school children of farmers, anthroposophic families and controls and to evaluate the validity of a food questionnaire as part of a lifestyle questionnaire of the PARSIFAL-study. Methods. Food questionnaires were completed by the parents of the children. Validity was assessed with 24-h recalls performed as telephone interviews with a parent accompanied by the child. Results. Dietary habits were assessed among 14 901 children. Farm children consumed most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…No portion size was asked for given the known challenges of accurate reporting and that assessing portion size does not necessarily increase validity ( 5 ) . Consistent with studies which suggest that children younger than 8 years of age face difficulties in estimating portions, and studies that found weak to moderate correlations when portions were assessed with children younger than 12 years of age ( 5 , 13 , 19 , 20 ) , our study did not measure portion sizes.…”
Section: Methodssupporting
confidence: 84%
“…No portion size was asked for given the known challenges of accurate reporting and that assessing portion size does not necessarily increase validity ( 5 ) . Consistent with studies which suggest that children younger than 8 years of age face difficulties in estimating portions, and studies that found weak to moderate correlations when portions were assessed with children younger than 12 years of age ( 5 , 13 , 19 , 20 ) , our study did not measure portion sizes.…”
Section: Methodssupporting
confidence: 84%
“…A total of 11 studies examined both reliability and validity. Ordered by publication year, Table 2 (26,36,42), France (29), Austria (34), Germany (34), the Netherlands (43), Sweden (34), Switzerland (34), Denmark (38), Iceland (38), Norway (38), Portugal (38), and Spain (38). Ten articles were from the United States (28,(30)(31)(32)(33)35,39,40,44,45).…”
Section: Resultsmentioning
confidence: 99%
“…In 12 publications the FFQs assessed intake of specific types of foods: ''beverages'' (33), ''beverages and fast foods'' (28,32), ''beverages and snacks'' (31), ''fruits and vegetables'' (25,27,43), ''fruit, vegetables, and juice'' (30,28,39), ''high fat/calories, fruit, vegetables, and grains'' (35), and ''sugary snacks'' (37). The remaining 9 studies focused on ''all aspects'' of diet (26,29,34,36,(40)(41)(42)44,45). The size of the FFQs varied from 6-152 items ((36,37), respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The five food categories in the FFQ results are defined according to the WHO definition of fruit and vegetables ( 15 ). However, legumes were added to three food categories to allow comparison with other fruit and vegetable FFQs ( 42 , 43 , 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%